2021
DOI: 10.1007/s10815-020-02058-0
|View full text |Cite
|
Sign up to set email alerts
|

Induction of spermatogenesis in men with hypogonadotropic hypogonadism

Abstract: Purpose We compared our clinical experience to international standards, assessed by response to treatment and pregnancy rates to ensure our results were comparable. Methods Men presenting with azoospermia related to hypogonadism were recruited into a treatment programme which was managed by one person over 8 years in a secondary care facility. Treatment followed published management plans using urinary gonadotropins. Data were collected on success rates in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Nonsignificant increases in assisted conception pregnancy rates were noted in men having a varicocelectomy compared to an embolisation (clinical pregnancy rate OR: 2.07; 95%CI: 0.92-4.65; P = 0.08) [24] . Meta-analyses, however, support varicocele repair in advance of assisted conception [25] .…”
Section: Hypogonadism In Men Leading To Infertilitymentioning
confidence: 99%
“…Nonsignificant increases in assisted conception pregnancy rates were noted in men having a varicocelectomy compared to an embolisation (clinical pregnancy rate OR: 2.07; 95%CI: 0.92-4.65; P = 0.08) [24] . Meta-analyses, however, support varicocele repair in advance of assisted conception [25] .…”
Section: Hypogonadism In Men Leading To Infertilitymentioning
confidence: 99%
“… 14 Like FSH and LH, cost varies substantially, with 1 study reporting a monthly cost of$359 while pharmacies within our study reported monthly costs of less than$75 USD per month. 15 …”
Section: Introductionmentioning
confidence: 99%